241. Rural-urban differences in antibiotic prescribing for uncomplicated urinary tract infections. (31st December 2020) - Clark, Abbye W; Durkin, Michael; Olsen, Margaret A; Keller, Matthew R; Ma, Yinjiao; Butler, Anne M
Abstract: Background: Identification of inappropriate antibiotic prescribing patterns is critical for designing antimicrobial stewardship programs. We sought to examine whether the risk of receipt of an inappropriate outpatient antibiotic prescription varied by rural-urban status among women with an uncomplicated urinary tract infection (UTI). Methods: Using the IBM MarketScan Commercial Database, we identified U.S. women 18–44 years diagnosed with a new uncomplicated UTI and prescribed an oral antibiotic with activity against common uropathogens from April 2011 through June 2015. We classified first-line agents (nitrofurantoin, trimethoprim-sulfamethoxazole, and fosfomycin) as appropriate, non-first-line agents (fluoroquinolones and β-lactams) as inappropriate, and antibiotic duration as appropriate when the days' supply was consistent with Infectious Diseases Society of America 2011 guidelines. Rural-urban status was defined by residence in a metropolitan statistical area. We used modified Poisson regression to determine the association between rural-urban status and inappropriate antibiotic receipt, accounting for patient- and provider-level characteristics. Results: Of 670, 450 women with uncomplicated UTI, 46.7% of antibiotic prescriptions were written for inappropriate agents and 76.1% for inappropriate durations (Figures 1 and 2). Use of inappropriate agents or durations did not change appreciably over the study period (2011–2013 vs. 2014–2015). Of 507, 737 prescriptions with inappropriate duration, 501, 496 (98.8%) were written for a days' supply longer than recommended. Compared to urban women, rural women had similar risk of receipt of an inappropriate agent (adjusted risk ratio 0.99, 95% CI, 0.98–1.00) but were more likely to receive a prescription for an inappropriate duration (adjusted risk ratio 1.10, 95% CI, 1.09–1.11). Figure 1. Distribution of antibiotic agent by rural-urban status Figure 2. Distribution of the antibiotic prescription days' supply by antibiotic agent and rural-urban status Conclusion: Regardless of rural-urban status, the majority of antibiotic prescriptions for uncomplicated UTI were written for inappropriate agents and durations. Rural women were more likely to receive prescriptions with inappropriately long durations. Antimicrobial stewardship interventions are needed to improve outpatient UTI antibiotic prescribing and reduce unnecessary exposure to antibiotics, particularly in rural settings. Disclosures: Margaret A. Olsen, PhD, MPH, Merck (Grant/Research Support)Pfizer (Consultant, Grant/Research Support)